Demand-side barriers and economic burden in accessing Human Papillomavirus screening for cervical cancer prevention in rural India: Evidence from a cross-sectional study [version 2; peer review: 1 approved, 2 approved with reservations, 2 not approved] - Swetha Chandrasekar; Arun Daniel Jayakumar; Pavan Kumar Gollapalli; Shyamkumar Sriram (F1000Research)
Introduction Cervical cancer is a significant global health concern, especially in low- and middle-income countries with limited access to preventive healthcare. India’s vast rural population amplifies the challenge, demanding immediate action. Despite advancements, cervical cancer remains prevalent among underserved rural communities, hindered by barriers to Human Papillomavirus (HPV) screening uptake, including socioeconomic and financial constraints. This study aims to evaluate the economic challenges encountered by rural women when accessing HPV screening. Methods A cross-sectional survey was conducted among 1502 women aged 30 to 45 in Pondicherry, India, utilizing the Andersen Model as a conceptual framework. Household questionnaires gathered data on HPV screening expenses, including patient travel costs, productivity loss, and companion costs. The analysis utilized regression models, to identify the factors impacting the economic challenges associated with accessing HPV screening. Results The study found that employment status significantly influenced healthcare costs, with employed women incurring ₹65.78 more than unemployed women (p < 0.001). Education level was also a significant predictor, with each additional year of education leading to a ₹108.45 increase in costs (p < 0.001). Travel time had a positive association with healthcare costs, with every additional minute spent traveling increasing costs by ₹5.98 (p < 0.001). Income and companion accompaniment were also significant predictors, while distance to the PHC and age did not show significant associations with total healthcare. Conclusions The study highlights the multifaceted economic challenges faced by rural populations accessing HPV screening for cervical cancer prevention in India. Notwithstanding diverse demographics and varying proximity to healthcare facilities, individuals encounter significant barriers such as travel time and associated costs. Addressing these challenges necessitates targeted interventions to reduce socioeconomic disparities and improve healthcare accessibility for vulnerable populations, thereby advancing cervical cancer prevention efforts and promoting health equity in rural communities.